2020
DOI: 10.1192/j.eurpsy.2020.23
|View full text |Cite
|
Sign up to set email alerts
|

Autism trait prevalence in treatment seeking adolescents and adults attending specialist gender services

Abstract: Background. To assess the prevalence of autism traits in individuals accessing gender affirming treatments, we conducted a cross-sectional survey in the regional specialist gender services in Northern Ireland. Methods. One hundred and twenty-three individuals (38 adolescents and 69 adults) currently attending or who previously attended specialist gender services in Northern Ireland were recruited. Fifty-six individuals assigned male at birth (AMAB) and 66 individuals assigned female at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…To examine the prevalence of ASD caseness in GD/GI cohorts, researchers have relied on cutoff scores from ASD screening questionnaires. Studies have shown that the positive rates for ASD range from 14.5 to 68% in GD/GI children and adolescents (Akgül et al, 2018;Leef et al, 2019;Mahfouda et al, 2019;Shumer et al, 2016;Skagerberg et al, 2015;VanderLaan, Leef, et al, 2015;van der Miesen, de Vries, et al, 2018) and from 1.2 to 40.3% in GD/GI adults (Heylens et al, 2018;Jones et al, 2012;Kristensen & Broome, 2015;Lehmann et al, 2020;Murphy et al, 2020;Nobili et al, 2018;Nobili et al, 2020;Pasterski et al, 2014;Stagg & Vincent, 2019;Vermaat et al, 2018). However, the incidence of ASD caseness ranges widely depending on the cutoff scores used.…”
Section: Prevalence Of Asd Casenessmentioning
confidence: 99%
“…To examine the prevalence of ASD caseness in GD/GI cohorts, researchers have relied on cutoff scores from ASD screening questionnaires. Studies have shown that the positive rates for ASD range from 14.5 to 68% in GD/GI children and adolescents (Akgül et al, 2018;Leef et al, 2019;Mahfouda et al, 2019;Shumer et al, 2016;Skagerberg et al, 2015;VanderLaan, Leef, et al, 2015;van der Miesen, de Vries, et al, 2018) and from 1.2 to 40.3% in GD/GI adults (Heylens et al, 2018;Jones et al, 2012;Kristensen & Broome, 2015;Lehmann et al, 2020;Murphy et al, 2020;Nobili et al, 2018;Nobili et al, 2020;Pasterski et al, 2014;Stagg & Vincent, 2019;Vermaat et al, 2018). However, the incidence of ASD caseness ranges widely depending on the cutoff scores used.…”
Section: Prevalence Of Asd Casenessmentioning
confidence: 99%
“…The connection with others is a core support for individuals and socialization was a topic examined by eight papers (Cooper, Mandy, et al., 2023 ; Janssen et al., 2016 ; Kahraman et al., 2021 ; Kuvalanka et al., 2018 ; Lehmann et al., 2020 ; Mahfouda et al., 2019 ; Russell et al., 2021 ; Shumer et al., 2016 ). Many studies highlighted that autistic individuals have challenges with communication and cognitive flexibility, which contributed to difficulties in understanding social situations and conventions (Mahfouda et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parallel to this, several studies suggest that given the clear overrepresentation of autism in trans persons, it should be standard practice for all gender clinicians to screen for autistic traits in all youth who are seeking gender affirmation services, including gender affirming medical care (Lehmann et al., 2020 ; Russell et al., 2021 ). They surmise that as autistic traits often require substantial supports, if autism is identified by gender clinicians early in the process, more wholistic treatments, including gender affirming medical care/interventions, will benefit the person and provide an overall improvement to mental health and wellbeing (Cooper, Mandy, et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GIFTS (Gender Identity-Finding and Transforming Services) is a mixed methods project, with findings from an associated prevalence study reported elsewhere (Lehmann et al, 2020). The qualitative study undertaken here examines the experiences of both users of specialist gender services (Knowing Our Identity-Gender Identity Development Service & Brackenburn Clinic) in Northern Ireland (NI), and a small community-derived sample of individuals living with gender-related distress.…”
Section: The Gifts Studymentioning
confidence: 99%